Perdus dans l’espace : survivre à la mondialisation dans Gravity et Seul sur Mars - Siobhan Carroll (ReS Futurae, 2021)
The Martian (2015) and Gravity (2013) join a group of recent maritime disaster films in depicting American individuals struggling to survive in hostile natural environments. Noting the ocean’s historical function as a signifier of internationalism, this essay examines these science-fictional stories of shipwreck in space as expressions of anxiety in the face of globalization. Where The Martian promotes a vision of the resilience of American skilled labor, Gravity portrays the emotional consequences of the isolation produced by globalization’s network culture. Both films ultimately, however, urge acceptance of a global economic system in which, by virtue of the international distribution of movie production, the film’s creators are invested. Examining the spatial politics of Gravity and The Martian allows us to see not only the filmmakers’ attempts to negotiate the anti-globalization backlash of the 2010s, but also the way in which ostensibly neutral natural spaces convey political and cultural meaning.